2013
DOI: 10.1590/s0103-21002013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Expectativas da equipe de enfermagem em relação à liderança

Abstract: Objectives: To identify the expectations of the nursing staff in relation to the leadership of a future manager. Methods: This was an exploratory, descriptive research study, conducted in a university hospital. Data were collected by means of semi-structured interviews with 62 professionals in the field of nursing. The transcribed interviews were analyzed according to the reference of content analysis. Results: Four categories of expectations emerged from the analysis: the behavior of the future manager, worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
0
7
0
10
Order By: Relevance
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 93%
“…When analyzing the expectations of nursing teams in face of leadership, the interviewed professionals mentioned that future leaders need to be people who allow frank and open communication, have the capacity to recognize and attend to the needs of teams, know how to give support when needed, and seek harmony in the work environment, working for the union and integration of the group and ensuring the satisfaction of those led. (33) Ten other studies (10,11,(14)(15)(16)18,(20)(21)(22)34) showed positive and significant, direct correlations between the different leadership styles analyzed and job satisfaction; that is, as leadership is exercised and perceived, there is an increase in job satisfaction. The influence of leadership style in the work environment is well-known, because it can lead to synergy or disintegration of teams.…”
Section: Discussionmentioning
confidence: 93%
“…This condition helps the groups to face situations which change constantly, assisting in the recognition of those in whom one can trust and on whom one can rely in order to overcome difficulties (10)(11) .…”
Section: Motivation For Taking On the Management Positionmentioning
confidence: 99%
“…The verbalizations on this issue denote contradictions, as, at the same time that interpersonal relationships are mentioned as stimulating and motivating, due to the diversity, they The emphasis on the challenge of working with people, that is, the organizations' human capital, has been indicated in various studies (11,14) . It is added that investing in the individual and collective potential in the work groups can help in the construction of more creative and innovative management models, able to respond to the constant transformations of settings in the health systems.…”
Section: The Emblematic Aspect Of Working With Peoplementioning
confidence: 99%
“…1,7 Moreover, in working with different professions, the communication between the teams favors the approximation of the different fields of knowledge in the professional relationship, allows exchanges of knowledge and facilitates the understanding of each professional about their role in patient care. 8 However, it has been observed in the nursing work process that sometimes the communication can be used as a tool for consolidation of autocratic leadership models that reproduce the technical and social division of nursing work and not in line with contemporary management paradigms which presuppose horizontalization, flexibility and insert human relations as an essential component to organizational success. [9][10] The paradoxes found between what is proposed in the speech, predominantly served in academic environments, and what is perceived operationalized in practice aroused reflections on the use of communication as a possibility for changes and rearrangements of the nursing work in hospital context.…”
Section: Introductionmentioning
confidence: 99%